Evaluation of nanobody-based biologics targeting purinergic checkpoints in tumor models in vivo - Demeules, Mélanie; Scarpitta, Allan; Hardet, Romain; Gondé, Henri; Abad, Catalina; Blandin, Marine; Menzel, Stephan; Duan, Yinghui; Rissiek, Björn; Magnus, Tim; Mann, Anna Marei; Koch-Nolte, Friedrich; et al. (Frontiers in Immunology, 2022)
Adenosine triphosphate (ATP) represents a danger signal that accumulates in injured tissues, in inflammatory sites, and in the tumor microenvironment. ATP promotes tumor growth but also anti-tumor immune responses notably via the P2X7 receptor. ATP can also be catabolized by CD39 and CD73 ecto-enzymes into immunosuppressive adenosine. P2X7, CD39 and CD73 have attracted much interest in cancer as targets offering the potential to unleash anti-tumor immune responses. These membrane proteins represent novel purinergic checkpoints that can be targeted by small drugs or biologics. Here, we investigated nanobody-based biologics targeting mainly P2X7, but also CD73, alone or in combination therapies. Blocking P2X7 inhibited tumor growth and improved survival of mice in cancer models that express P2X7. P2X7-potentiation by nanobody-based biologics was not effective alone to control tumor growth but enhanced tumor control and immune responses when used in combination with oxaliplatin chemotherapy. We also evaluated bi-specific nanobody-based biologics that targets PD-L1 and CD73. This novel nanobody-based biologics exerted a potent anti-tumor effect, promoting tumor rejection and improving survival of mice in two tumor models. Hence, this study highlights the importance of purinergic checkpoints in tumor control and open new avenues for nanobody-based biologics that may be further exploited in the treatment of cancer.